Cyclical effects of credit conditions in a small open economy: the case of Peru (Capítulo) - Ortiz, Marco (2016)
In this chapter we extend a new Keynesian open economy model to include a housing market and credit constraints in line with Iacoviello (2005). This setup allows us to study the effect of changes in credit conditions, represented by the share of capital that agents can use as collateral for loans, in the business cycle. In our setup, the easing of credit conditions generates a downward pressure on inflation, higher housing prices, a GDP expansion and a real depreciation. Additionally, we analyze how the presence of credit constrained firms affects optimal monetary policy rules. We find that in the presence of exogenous shocks to credit conditions and pecuniary externalities, the central bank obtains relatively small gains by reacting to fluctuations in asset prices. In contrast, the use of a different instrument that reacts to changes in the financial conditions can provide significant gains in stabilizing the economy. These results support the argument for using a different instrument for macroprudential purposes instead of the central bank policy rate.